Ответы и объяснения

  • IZUBR
  • светило науки
2013-01-01T15:12:58+04:00

x^{9lg^3(x)-11lgx}=0,01;\\ lgx*(9lg^3(x)-11lg(x))=lg(0,01);\\ lg(0,01)=log10(1/100)=log10(10)^-2=-2;\\ 9lg^4(x)-11lg^2(x)=-2;\\ lg^2(x)=y;\\ 9y^2-11y+2=0;\\ D=121-72=49;\\ y1=1;\\ y2=2/9;\\ lg^2(x)=1;\\ lgx=1; lgx=-1;\\ x=10^1; x=10^-1;\\ x=10; x=1/10;\\ lg^2(x)=2/9;\\ lgx=\sqrt{2}/3; lgx=-\sqrt{2}/3\\ x=10^{\sqrt{2}/3}; x=10^{-\sqrt{2}/3};

 Сначала мы логарифмируем, опуская степень вниз:

lgx*(9lg^3(x)-11lg(x))=lg0,01;

Т.к. lg0,01=log10(0,01)=log10(1/100)=log10(10)^-2=-2;Т.к. loga(a)^r=r;

9lg^4(x)-11lg^2(x)=-2;

Делаем замену, lg^2(x)=y;

9y^2-11y+2=0;

D=49;

y1=1;

y2=2/9;

Возвращаемся в замену:

lg^2(x)=1;

lgx=1;

x=10;

lgx=-1;

x=10^-1;

x=1/10;

lg^2(x)=2/9;

lgx=+/-2/3;

lgx=2/3;

x=10^(2/3);

lgx=-2/3;

x=10^(-2/3);

Ответ:

x=10;x=1/10;x=10^(2/3);x=10^(-2/3);